MORPHOLOGICAL CHANGES IN THE BRONCHI IN CHILDREN AGED 1 YEARS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The lungs of mammals are formed by a branched system, ending in gas exchange units known as alveoli. Although the total amount of atsinus does not change the development of the lungs of rats in the moboyne of the entire postnatal period, the lungs continue to develop even after birth, in which the area of the surface of the alveoli increases significantly during the postnatal period.